Epstein–Barr virus‐associated smooth muscle tumors in a composite tissue allograft and a pediatric liver transplant recipient. Issue 5 (27th August 2013) - Conrad, A.; Brunet, A.‐S.; Hervieu, V.; Chauvet, C.; Buron, F.; Collardeau‐Frachon, S.; Rivet, C.; Cassier, P.; Testelin, S.; Lachaux, A.; Morelon, E.; Thaunat, O.
Abstract: Epstein–Barr virus (EBV) is known to establish latent infections in B‐lymphocytes that can cause lymphoproliferative disorders particularly in immunocompromised patients. More recently, the development of rare EBV‐associated smooth muscle tumors has been reported in transplant recipients. We herein describe 2 new cases of EBV‐associated post‐transplant smooth muscle tumors (EBV‐PTSMT), including the first in a facial composite tissue graft recipient. Among the striking features shared by these 2 patients were their young ages, the fact that they were naïve for EBV before the transplantation, that they developed a post‐transplant lymphoproliferative disorder before the diagnosis of EBV‐PTSMT, and that they responded favorably to reduction of immunosuppression. Radiological and histologic features of EBV‐PTSMT are shown. Finally, pathophysiology and therapeutic management of EBV‐PTSMT are discussed based on a comprehensive review of the literature.